Pemberdayaan Masyarakat dalam Pengembangan Desa Wisata di Dusun Plempoh, Desa Bokoharjo, Kecamatan Prambanan, Kabupaten Sleman, D.I Yogyakarta - Ma’arif, Bilal; Syakdiah, Syakdiah; Anggraini, Oktiva (Universitas Widya Mataram, 2019)
Community empowerment is basically an effort to make people able to actualize themselves in managing the cultural environment that is around them and fulfill their needs independently without dependence on other parties. In relation to cultural heritage, empowerment activities depart from the basic concept that the management of a cultural heritage needs to pay attention to its important value or social significance. In other words, the extent to which a cultural preservation is socially meaningful for its people. The process of empowering the Tourism Village in Plempoh Hamlet, Bokoharjo Village, Prambanan District, Sleman Regency, Yogyakarta. At the beginning of the program, the community awareness stage was carried out by pioneers of village empowerment with makeshift funds and there was no guidance from government agencies. Before Pokdarwis was formed, it was previously called Plempoh Tourism Village in 2010. Only in 2015 did Pokdarwis Plempoh be formed. Efforts made in utilizing the potential and skills possessed for the initial pilot. To identify potential as well as constraints on community empowerment related to the availability of regional cultural resources. Mapping the needs and forms of empowerment programs tailored to the needs of the community and the availability of supporting resources. The initial approach taken was a community-oriented approach in its implementation realized through empowering the community around the site. Broadly speaking, there are four types of technical training held, namely batik training, souvenir making training, culinary training and tour guide training and the development of cultural tourism travel businesses.